Monitoring Protocol to Assess the Overall Performance of Lighting and Daylighting Retrofit Projects. (November 2015) - Gentile, Niko; Dubois, Marie-Claude; Osterhaus, Werner; Stoffer, Sophie; Amorim, Cláudia Naves David; Geisler-Moroder, David; Hoier, Anna; Jakobiak, Roman
Abstract: In the field of lighting and daylighting, standard monitoring procedures to assess the overall performance of retrofit projects are scarce. Nevertheless the access to monitored data is crucial to assess whether daylighting or electric lighting systems deliver the expected performance in terms of cost-effectiveness and energy efficiency. In order to bridge this gap, a monitoring protocol is under development as part of the International Energy Agency – Solar Heating and Cooling Programme (IEA-SHC) Task 50 'Advanced Lighting Solutions for Retrofitting Buildings'. The protocol focuses on lighting and/or daylighting (façade or roof) retrofit in the non-residential building stock. It covers four key aspects: energy efficiency, costs, quality of the lighting environment and user satisfaction. The main features of this protocol are presented in this paper, along with some lessons learned from the ongoing application on selected case studies.